Comparative Anatomy Of Leaves Of Several Types Of Ficus - Euis F. S. Pangemanan; Semuel P. Ratag; Marthen T. Lasut (Sam Ratulangi University, 2022)
Leaf anatomy studies need to be carried out to support morphological plant identification. Leaf anatomy was observed because leaves have varying tissue structures. The characteristics of stomatal density, epidermal cell shape, and leaf mesophyll structure are constant in each species so that they can be used as a reference. The aim of the study was to identify the anatomical characters of the leaves of various types of Ficus. Samples were collected from Tahura Gunung Tumpa. Observation of the anatomical structure of Ficus leaves using a light microscope based on Sass (1951) and Johansen (1940) and carried out at the Laboratory of Plant Structure and Development, Faculty of Biology UGM. Data analysis was carried out descriptively and presented in the form of tables and figures. Leaf anatomy observations were carried out on 19 Ficus species found in TAHURA Gunung Tumpa, namely Ficus fistulosa, F. forstenii, F. microcarpa, F. ampelas, F. septica, F. tinctoria, F. variegata, F. benjamina, F. subulata , F. punctata, F. elegans, F. hispida, F. racemose, F. elastica, F. minhassae, Ficus sp1, Ficus sp2, Ficus sp3, and Ficus sp4. Based on the location of the hypodermis, 3 groups of Ficus were found, namely: species with hypodermis located on one side, species with hypodermis located on both sides, and species without hypodermis. Based on the presence or absence of a vessel sheath in the mesophyll, Ficus is divided into 2 groups, namely having and not having a vessel sheath. Lithocyte cells were found in all Ficus leaves observed, with various shapes and locations. Conclusion. The anatomical character of Ficus leaves differs between species Keywords: Ficus, comparative anatomy, leaves Abstrak Studi anatomi daun perlu dilakukan untuk mendukung identifikasi tanaman secara morfologi. Anatomi daun diamati karena daun memiliki struktur jaringan yang bervariasi Karakteristik kerapatan stomata, bentuk sel epidermis, dan struktur mesofil daun bersifat konstan pada setiap spesies sehingga dapat dijadikan acuan. Tujuan penelitian untuk mengidentifikasi karakter anatomi daun berbagai jenis Ficus. Sampel dikumpulkan dari Tahura Gunung Tumpa. Pengamatan struktur anatomi daun Ficus menggunakan mikroskop cahaya berdasarkan Sass (1951) dan Johansen (1940) dan dilakukan di Laboratorium Struktur dan Perkembangan Tumbuhan, Fak Biologi UGM. Analisis data dilakukan secara deskriptif dan disajikan dalam bentuk tabel dan gambar. Pengamatan anatomi daun dilakukan pada 19 spesies Ficus yang ditemukan di TAHURA Gunung Tumpa, yaitu Ficus fistulosa, F. forstenii, F. microcarpa, F. ampelas, F. septica, F. tinctoria, F. variegata, F. benjamina, F. subulata, F. punctata, F. elegans, F. hispida, F. racemose, F. elastica, F. minahassae, Ficus sp1, Ficus sp2, Ficus sp3, dan Ficus sp4. Berdasarkan letak hipodermis, ditemukan 3 kelompok Ficus yaitu : jenis dengan hipodermis terletak pada salah satu sisi, jenis dengan hipodermis terletak pada kedua sisi, dan jenis yang tidak memiliki hipodermis. Berdasarkan ada tidaknya seludang pembuluh pada mesofil, Ficus dibagi dalam 2 kelompok yaitu memiliki dan tidak memiliki seludang pembuluh. Sel litosit ditemukan pada semua daun Ficus yang diamati, dengan bentuk dan lokasi yang beragam. Kesimpulan: karakter anatomi daun Ficus berbeda diantara jenis. Kata kunci: Ficus, anatomi perbandingan, daun